Analisis keterampilan berpikir kritis ditinjau dari gaya belajar pada materi penjumlahan dan pengurangan bilangan pecahan peserta didik kelas iv sekolah dasar - Vita Astarini; Idam Ragil Widianto admojo; Hasan mahfud; Anesa Surya (Universitas Sebelas Maret, 2024)
The aim of this research is to describe critical thinking skills in terms of learning styles on the topic of addition and subtraction of fractions among fourth-grade students at SDN Tegalrejo No. 98 in the academic year 2023/2024. This study employs a qualitative research method with a case study design. The subjects are teachers and nine fourth-grade students from SDN Tegalrejo No. 98. Data collection techniques include questionnaires, interviews, observations, and documentation. Data validity is ensured through triangulation of techniques and sources. Data analysis follows Creswell's analytical model. The results indicate that students with kinesthetic and auditory learning styles were only able to fulfill the evaluation and inference indicators. Students with a visual learning style did not meet all four indicators of critical thinking skills, including interpretation, analysis, evaluation, and inference. Therefore, this research is expected to provide additional information for teachers to develop more effective and efficient teaching strategies by considering students learning styles. Additionally, it serves as a reference for further research on mathematics learning. The implication of this research is that critical thinking skills play a crucial role in solving mathematical problems related to addition and substraction of fractions.